New Economic Training Model for Installing Ultrasound-Guided Drainages - Mohr, A.; Jung, E. M.; Stroszczynski, C.; Schacherer, D.; Klebl, F. (Zeitschrift für Gastroenterologie, 2014)
Abscesses and circumscribed collections of fluid are frequently found as complications of infectious diseases or surgery. Drainage is often indicated. We have established a new, economic, easy-to-make model to learn and improve competence in installing ultrasound-guided drainage. Up to fifteen water balloons (size 30 – 50 mm) were placed in a plastic box which then was filled with instant custard powder mixed with water. Spiral computed tomography (CT) of this box was performed. Experienced (n = 8) and inexperienced examiners (n = 8) drained the balloons via a direct puncture technique using either ultrasound-guidance alone or volume navigation with image fusion (ultrasound and CT) with needle tracking. Trainees filled out a questionnaire (before and after training) asking for information on their experience in ultrasound, in installing drainages and evaluating the new model. The time needed for installing the drainage was measured. None of the participants had ever attended a course on drainage installation. Only a few of the experienced examiners (n = 3) would autonomously install a drainage into a fluid collection with a size exceeding 4 cm before training. After training all participants felt more confident in ultrasound and in installing drainages into abscesses or other fluid collections. Most of the participants rated additional volume navigation with image fusion as a helpful tool. Ultrasound-guided drainage of abscesses can be trained easily with this new and economic model. Students and physicians can improve their skills and gain confidence in performing ultrasound-guided interventions.
Keywords: ultraschallgesteuerte Drainage; Intervention; Volumennavigation; Abszesse; Drainage; Trainingsmodell